2010
DOI: 10.4038/engineer.v43i4.6997
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Duration of Road Construction Projects in Sri Lanka

Abstract: This study attempts to reveal the factors influencing the duration of road construction projects in Sri Lanka, and to identify how delays can be mitigated. The emphasis here is limited to study the Contractor's point of view. The main concern of the study is to identify the nature of the population (Road projects in Sri Lanka) using Statistical Inference. The other focusing areas are to identify Main Causes of Delay & Delay Diversification, and Delay Mitigation. This study defines the Percentage Delay paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…A study by Halwatura and Pathiranage revealed that locally based road construction projects in Sri Lanka experience between 56% and 88% of average time overrun compared to planned project duration as a result of financial problems on the part of the owner (client) and the contractor [35]. The findings resonate with Mushori et al who found that road performance is correlated with financial ability [17].…”
Section: Client Supportmentioning
confidence: 81%
“…A study by Halwatura and Pathiranage revealed that locally based road construction projects in Sri Lanka experience between 56% and 88% of average time overrun compared to planned project duration as a result of financial problems on the part of the owner (client) and the contractor [35]. The findings resonate with Mushori et al who found that road performance is correlated with financial ability [17].…”
Section: Client Supportmentioning
confidence: 81%
“…One of the most important problems in the road construction industry in Sri Lanka seems to be managing variation orders. There is less literature available on this area; however, Pathiranage and Halwatura [12] have found in their study that one of the main causes of project delay is variation orders. Moreover, Nowfal and Gunawardana [13] stated that the variation order is a key factor which is contributing to price overrun in this industry.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…Moreover, there several studies have the semilar result and support with above review findings accordingly (Rahman, Lee, & Ha, 2014), (Mahamid, 2013), (Rafieizonooz, 2012), (Albogamy, Scott, & Dawood, 2012). (Pourrostam & Ismail, 2012), (Pathiranage, 2011), (Enshassi, Al-Najjar, & Kumaraswamy, 2009) (Toor & Ogunlana, 2008). (Assaf & Al-Hejji, 2006).…”
Section: Empirical Review Findingsmentioning
confidence: 99%